TRINITAS DAN SIFAT TUHAN: Studi Analisis Perbandingan Antara Teologi Kristen dan Teologi Islam - Dahlia, Sri (Jurnal Penelitian, 2017)
This paper emphasizes discussion on two traditions of Abrahamic religion, Islam and Christian who have more or less the same doctrine. Among these doctrinal similarities are the attributes of God. Various schools in Islamic theology differ on the existence of such attributes. Some say qadim and some say hadithas well as in the Christian tradition. In addition, this paper also elaborates the Mu’tazilite opinion that believes that the atributes of God as hadith contrasts with the opinion of Ash’ariyah. While in the Christian tradition that has a doctrine similar to the Mu’tazila is the understanding of the humanity of Jesus.